2008
DOI: 10.1090/s0002-9939-08-09767-0
|View full text |Cite
|
Sign up to set email alerts
|

On some permutation polynomials over $\mathbb {F}_q$ of the form $x^r h(x^{(q-1)/d})$

Abstract: Abstract. Several recent papers have given criteria for certain polynomials to permute F q , in terms of the periods of certain generalized Lucas sequences. We show that these results follow from a more general criterion which does not involve such sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(74 citation statements)
references
References 31 publications
0
74
0
Order By: Relevance
“…The following lemma, which will be used to prove our main results, was proved by Park The polynomials of the form x r h(x) s have been widely studied, see [1,19,20,22,25,26] for example.…”
Section: Preliminariesmentioning
confidence: 96%
“…The following lemma, which will be used to prove our main results, was proved by Park The polynomials of the form x r h(x) s have been widely studied, see [1,19,20,22,25,26] for example.…”
Section: Preliminariesmentioning
confidence: 96%
“…Finding new PPs and CPPs of finite fields is a difficult problem and there are rare classes of CPPs known. For more study of PPs and CPPs can be found in [1][2][3][4]6,9,10,15,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The subset of such bijective mappings was characterized by Zieve in [13]. Lemma 1 is the binary version of [13, Lemma 2.1].…”
Section: On Differential Spectrum Of a Class Of Permutationsmentioning
confidence: 99%
“…In Section 3 we show that the differential spectrum of a class of permutations described by Zieve [13] is determined by a small number of derivatives (Theorem 6). Finally we focus on binomials and give some numerical results.…”
Section: Introductionmentioning
confidence: 99%